Environmental implications of geohazard analysis in a climatically variable arid region: A case study of the Al-Mutla'a-Al-Jahra Coastal Plain, State of Kuwait (Kuwait Journal of Science)
This study addresses the pressing need for integrated environmental management in Kuwait's central coastal arid zone, which faces increasing environmental challenges due to extensive human activities and climate change. The research employs remote sensing (RS), geographic information systems (GIS), land use and land cover (LU/LC) change detection, watershed analysis, and fieldwork to assess both regional paleo-drainage systems and local basins. The findings identify Al-Jahra and Al-Mutlla'a as areas highly susceptible to flash flooding and Al-Mutlla'a to sand encroachment. Morphometric analysis indicates that regional basins such as B2, B3, and B4 exhibit moderate drainage densities (0.37–4.9) and elongated shapes, which mitigate flash flood risks. In contrast, local basins like Jal-Az-Zor and Jal-Al-Atraf have higher drainage densities (1.9–2.4), steep slopes (>45°), and elevated relief ratios (19.13–20.4), making them more vulnerable to flash floods and erosion. Urbanization analysis reveals a 33.7 % expansion in urban areas between 1986 and 2021, with a notable acceleration from 2013 to 2021 at a rate of 10 km2 per year. Additionally, sand movement and land-use changes have heightened landscape instability, particularly in inland desert dune fields, which remain highly dynamic. The findings highlight the need for tailored land management policies, including proposed trenching projects around Al-Jahra and integrated environmental management plans to enhance resilience against these hazards and support sustainable development. © 2025 The Authors